High‐performance radiofrequency coils for 23Na MRI: brain and musculoskeletal applications. (24th September 2015) - Wiggins, Graham C.; Brown, Ryan; Lakshmanan, Karthik
Abstract : 23 Na RF coil design for brain and MSK applications presents a number of challenges, including poor coil loading for arrays of small coils and SNR penalties associated with providing 1 H capability with the same coil. The basics of RF coil design are described, as well as a review of historical approaches to dual tuning. There follows a review of published high performance coil designs for MSK and brain imaging. Several coil designs have been demonstrated at 7T and 3T which incorporate close‐fitting receive arrays and in some cases design features which provide 1 H imaging with little penalty to 23 Na sensitivity. The "nested coplanar loop" approach is examined, in which small transmit‐receive 1 H elements are placed within each 23 Na loop, presenting only a small perturbation to 23 Na performance and minimizing RF shielding issues. Other designs incorporating transmit‐receive arrays for 23 Na and 1 H are discussed including a 9.4 T 23 Na / 1 H brain coil. Great gains in 23 Na SNR have been made with many of these designs, but simultaneously achieving high performance for 1H remains elusive. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : The current state of the art of radiofrequency (RF) coil design for 23 Na brain and musculoskeletal imaging is reviewed. Coil design for 23 Na presents various challenges, particularly if it is also desired for the coil to provide 1 H imaging. Through close attention to coil loading and by minimizing unwanted RF shielding, high sensitivity to 23 Na can be achieved, whilst also providing 1 H sensitivity more than adequate for shimming and anatomical localization.